Numerical approach of wellbore stability and minimum required mud weight - Hassan Adel Abdelhameed Sheha; Abdelalim Hashem Elsayed (Cairo : Hassan Adel Abdelhameed Sheha, 2018)
Wellbore stability studies need combination of various backgrounds to be able to commingle between the petroleum geology, geophysics, and drilling engineering. Besides, building a computerized model needs programming skills and sufficient time for modification to finalize a successful, reliable, and usable program. Therefore, Microsoft Excel will be used to accomplish the wellbore stability model as a numerical approach, which will provide various flexible options of editing, and provide a simple window for use for engineers. Using the numerical model during planning phase of new well, results in drilling stable hole regarding stresses state. That reflects in saving cost and time
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Metallurgical Engineering
Issued also as CD
Keywords: Geo-mechanics; Modeling; Stability